Cultivating Creative Spirit Leadership in Assalam Sukoharjo High School Students: A Practical and Effective Approach - Nur Cholidah; Shodiq Purnomo; Harun Joko Prayitno; Indri (Bulletin of Science Education, 2024)
The study aims to explore practical and effective approaches to cultivating the spirit of creative leadership in students at Assalam Students High School in Sukoharjo. With a focus on the Islamic-based school context, this approach integrates religious principles with concepts of creative leadership. Through a combination of theory and practice, this article discusses concrete steps that can be implemented by teachers and school staff to build creative leadership skills in students. Using observation methods, interviews, and documentation analysis, this study highlights the success of certain strategies that have been implemented at PPMI Assalam Sukoharjo. Research results show that practical approaches involving project-based learning, teamwork, and empowering students in decision-making have successfully improved students' creative leadership skills. The practical implications of this study include recommendations for the development of curricula that support the growth of creative leadership, training for teachers in the application of innovative teaching methods, and collaborative efforts between schools, parents, and communities to create an environment that stimulates creativity and leadership in high school students. Thus, this article contributes to a practical understanding of how to cultivate the spirit of creative leadership in middle school students with an approach appropriate to the context of Islamic schools.